Green Marketing in the FMCG Sector: Consumer Perceptions and Behavioral Responses - Movva, Siva Sathyanarayana; Gujar, Vivek (Journal of Global Economy, Business and Finance, 2025)
The research study is on green marketing but exactly on customer’s preference & the factors that effect on purchasing an eco-friendly product. Green marketing is a process of producing environment friendly product. Such type of products those are safe from different hazards. Now a days Green marketing is exploring day by day. The eco-friendly products are making by many companies in Globe. Our Purpose of this study is basically to identify that what kind of factors influence the green purchase intentions of consumer of Hyderabad. Four preceding factors influence the consumer’s purchase intentions based green marketing. By using self-administered questionnaires we collected data from our 160 respondents. For regression analysis we entered all that data into SPSS and do analysis also. Results of our study show significant relationship of green purchase attitude. It has been the universal apprehension for the purpose of the protection of the poisoning and degradation of environment. This research has been undertaken to explore the importance of green marketing and relationship to the attitude and purchasing behaviour of the consumers of eco- friendly products. The objective of this research was looked into and travelled the persuading of the four old-style marketing-mix elements, satisfaction and purchasing intentions of consumers on environmental products precisely fast moving consumer goods (FMCG) or non-durable ones. The determination of the study was to obtain data from consumers’ point of view. A qualitative questionnaire was divided among sub groups cover 10-15 respondents. Furthermore, convenient sample was used as the sampling method. Our results showed that how customers are satisfied or their preference of green marketing and the factors that influence a customer to purchase a green brand such as; benefits, point of purchase (POP) & certification However, that positive in solences towards green products do not always lead to action buying of these products.